3D Porous Graphene by Low‐Temperature Plasma Welding for Bone Implants. Issue 40 (26th August 2016) - Chakravarty, Dibyendu; Tiwary, Chandra Sekhar; Woellner, Cristano F.; Radhakrishnan, Sruthi; Vinod, Soumya; Ozden, Sehmus; da Silva Autreto, Pedro Alves; Bhowmick, Sanjit; Asif, Syed; Mani, Sendurai A; Galvao, Douglas S.; Ajayan, Pulickel M.
Abstract : 3D scaffolds of graphene, possessing ultra‐low density, macroporous microstructure, and high yield strength and stiffness can be developed by a novel plasma welding process. The bonding between adjacent graphene sheets is investigated by molecular dynamics simulations. The high degree of biocompatibility along with high porosity and good mechanical properties makes graphene an ideal material for use as body implants.